Investigating Pre-service Indonesian EFL Teachers’ Foreign Language Teaching Anxiety in Teaching Practicum Activities - Kristian Wijaya (JELITA, 2022)
The primary objectivity of this current small-scale qualitative study was to profoundly investigate Indonesian EFL teachers’ foreign language teaching anxiety in teaching practicum activities. To reach this pre-determined research aim, 5 open-ended written narrative inquiry questions were administered to 2 English Education Master Students, batch 2020 of Sanata Dharma University, Yogyakarta. The research procedure employed in this present qualitative study was asking an agreement from the research participants, sending the online narrative inquiry questions, and subdividing the frequently-appeared research findings into specific themes. Drawing on the obtained research results, it was revealed that foreign language teaching anxiety experienced by pre-service Indonesian EFL teachers could potentially be alleviated in the support of suitable teaching practicum programs as well as ingenious self-management strategies. As a final note, supportive teaching practicum mentors’ supports, critical identification of foreign language teaching anxiety factors, appropriate teaching training, and education faculty programs are indispensably needed to progressively supersede excessive foreign language teaching anxiety with high-quality teaching performances.